Keluhan Nyeri Punggung Bawah Pada Nelayan - Novisca Prisicillya Kumbea; Oksfriani Jufri Sumampouw; Afnal Asrifuddin (Indonesian Journal of Public Health and Community Medicine, 2021)
Background: Fishermen are one of the coastal community groups who have public health problems, especially occupational health and safety, such as complaints of low back pain. Factors related to complaints of low back pain consist of several factors such as age, years of service, work attitude and others. The purpose of this study was to describe complaints of low back pain in fishermen in the Malalayang 1 Timur village, Manado city. Method: This is a descriptive study which was conducted in the Malalayang 1 Timur village, Manado city in January 2021 with 44 respondents. The variables in this study were complaints of low back pain, age, years of work and work attitude. The instruments used were questionnaires, cameras, and writing instruments. Data analysis was carried out by univariate. Results: The results of this study showed that the fishermen in the Malalayang Timur 1 Village are mostly in the age group of 20-44 years and 45-54 years, the working period is 16-25 years, the risk category for work attitude is very high and often experiences complaints of low back pain. The results of this study also indicate that the older the age, the longer the work period and the riskier work attitude, the more likely the respondent is to experience complaints of low back pain. Conclusion: This is can concluded the fishermen in the village of Malalayang 1 Timur, Manado city often experience complaints of low back pain. Therefore, it is necessary to make efforts to prevent and control it.